Evaluasi dan Perancangan Perbaikan Antarmuka Pengguna Aplikasi KER dengan Pendekatan Human Centered Design - Teophilus Hans Juliher; Ismiarta Aknuranda; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
KER is an e-government service for the Malang City government through the Malang City Information and Communication Office. KER is an integration of various public service applications to realize services in one hand. However, in its use, KER has several problems experienced by its users. Based on the problems found, researchers evaluated and designed user interface improvements to KER. Evaluation was carried out by measuring the success rate and time-based efficiency of 5 respondents using a task scenario then measuring the usability value obtained through the USE questionnaire (Usefulness, Satisfaction, and Ease of Use) filled out by 20 respondents after using the system. The approach used in the design is Human Centered Design. The designs produced in this study are a wireframe and a hi-fidelity prototype. In the initial evaluation, it was found that the success rate was 86.6%, the time-based efficiency was 0.05 goals / sec and the usability value was 65%. After improving the user interface design, a re-evaluation is carried out and it produces a success rate of 100%, a time-based efficiency of 0.01 goals / sec and a usability value of 82%. After the design improvement of the user interface design is carried out, an evaluation of the design improvement is carried out and results in a success rate of 100%, a time-based efficiency of 0.01 goals / sec and a usability value of 82%. Based on the results of the evaluation of user interface improvements, the improvements increase the usability value of the system.